Impact of Histidine Residues on the Transmembrane Helices of Viroporins - Wang, Yan (2013)
The role of histidine in channel-forming transmembrane (TM) helices was investigated by comparing the transmembrane helices from Virus protein ‘u’ (Vpu) and the M2 proton channel. Both proteins are members of the viroporin family of small membrane proteins that exhibit ion channel activity, and have a single TM helix that is capable of forming oligomers. The transmembrane helices from both proteins have a conserved tryptophan towards the C-terminus. Previously, alanine 18 of Vpu was mutated to histidine in order to artificially introduce the same HXXXW motif that is central to the proton channel activity of M2. Interestingly, the mutated Vpu TM resulted in an increase in helix tilt angle of 11° in lipid bilayers compared to the wild-type Vpu TM. Here, we find the reverse, when histidine 37 of the HXXXW motif in M2 was mutated to alanine, it decreased the helix tilt by 10° from that of wild-type M2. The tilt change is independent of both the helix length and the presence of tryptophan. In addition, compared to wild-type M2, the H37A mutant displayed lowered sensitivity to proton concentration. We also found that the solvent accessibility of histidine-containing M2 is greater than without histidine. This suggests that the TM helix may increase the solvent exposure by changing its tilt angle in order to accommodate a polar/charged residue within the hydrophobic membrane region. The comparative results of M2, Vpu and their mutants demonstrated the significance of histidine in a transmembrane helix and the remarkable plasticity of the function and structure of ion channels stemming from changes at a single amino acid site.